An experimental study into the capacity of cold-formed steel truss connections. (December 2016) - Zeynalian, Mehran; Shelley, Adele; Ronagh, H.R.
Abstract: This paper presents an experimental study on the behaviour of cold formed steel truss connections. Eighteen full scale cold-formed steel truss connections were tested. Of particular interests are the specimens maximum load capacity and the load-deformation behaviour. The study also looks at the failure modes of the connections. The behaviours exhibited by the connections are discussed and the design capacities calculated from the current CFS design standards are compared to the experimental results of the connections. This study investigates the main factors contributing to the ductile response of the CFS truss connections in order to suggest recommendations for connection designs, and improvements so that the connections respond plastically with a significant drift and without any risk of brittle failure. Also, a number of alternative fasteners are chosen and investigated for comparison with those that are currently specified for trusses' connections. Highlights: Cold formed steel connection Truss connection Experimental study Tearing failure Bearing